Rancang Bangun Sistem Pengamanan Mobil Menggunakan ID Card Dengan Metode Radio Frequency Identification - Muhammad, Rifki Habibi; Adi, Ridi Satrio (KOPERTIP : Jurnal Ilmiah Manajemen Informatika dan Komputer, 2017)
Conditions and progress in terms of technology is still not comparable with the behavior of people in certain circles, especially of motor vehicle theft both 4 wheel and 2 wheel, many methods are used by vehicle owners to secure ownership of the vehicle from theft is always lurking at any time wherever and whenever ironically even in the carport or in front of the house though theft can happen, even the manufacturer for certain cars have completed cars produced by security highly optimized, but what happens as though far from the fire, events have car theft is still rampant any places. Apparently the car security either manually or electronically is still easily estimated by thieves to break into its security after learning such weak points of certain cars. Events have made restless and uncomfortable car owners who always want the security and convenience in storing his car whenever it placed anywhere. The purpose of the above problems the author tried to make the design of the security system in the car using the id cards with radio frequency identification method. The method used in the making of this thesis consists of five stages, namely literature, field surveys, data analysis, design, and testing. The system is built using the Arduino Uno and RFID. This car security systems simply by using the id card / tag, can be lit when the car engine according to the database. For the owner of the car if it has no id card then the car will not be lit up and reducing material losses to owner. Research and design of security issues where the car has been successfully carried out when the car entered by either the owner or the borrower and have no IDCard / tag then the car will not turn on at all because the electrical source not connected to the start [1], the use of RFID Arduino Uno and in accordance with the original plan.